Just Politics: Bill Reading's Impertinent Call - Wagner, Valeria (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
In this article I argue that "impertinence" is one of the main strategies at work in Bill Reading's writings to disempower modernist metanarratives and their implicit universal subject. But if rendering these narratives impertinent (irrelevant) can "save" events from their totalizing grasp, the risk remains of rendering action itself impertinent to events.